Influencer marketing for brands : what YouTube and Instagram can teach you about the future of digital advertising - Levin, Aron (Marketing executive) (Apress, 2020)
In the next few years, brands are on track to spend billions of dollars on influencer marketing. This form of marketing--currently utilized with great success on Instagram and YouTube--is not a short-lived fad, but a tectonic shift for the future of digital advertising. It's the way of the future, and the responsibility is on business leaders to keep up. Modern marketing professionals looking to adopt influencer marketing for their brands face equally modern challenges. Like finding the right talent, tracking and measuring results and quantifying how this new marketing opportunity aligns with the overall strategy. Influencer Marketing for Brands is the field guide for the digital age. After working with hundreds of brands from across the globe, author Aron Levin shares his insider knowledge gained from research, strategy, and hands-on experience from more than 10,000 successful collaborations with influencers on Instagram and YouTube. He provides you with valuable insights that help you eliminate guesswork and avoid common mistakes. More importantly, he shows you how to turn influencer marketing into a scalable and sustainable marketing channel. The digital media landscape grows more complicated by the hour, and influencer marketing is no exception. Influencer Marketing for Brands breaks down the art and science of influencer marketing and helps you synthesize, contextualize and transform this new way of creating and distributing content with powerful formulas, proven strategies, and real-world examples. What You Will Learn Plan effective influencer marketing campaigns using a simple 3-step formula Create top performing YouTube videos that drive website traffic, app installs and sales Understand what to pay for influencer marketing and how much you should invest if you're just starting out Who This Book is For Marketing and agency professionals, influencers and content creators, marketing students, those who are looking for more effective forms of advertising and are generally interested in understanding the new and evolving digital media landscape.